Sleep-disordered breathing and daytime postural stability. Issue 6 (18th February 2016) - Degache, Francis; Goy, Yannick; Vat, Sopharat; Haba Rubio, José; Contal, Olivier; Heinzer, Raphaël
Abstract : Objective: Postural stability depends on the coordination of the central nervous system with visual sense, proprioceptive and vestibular information. Sleep deprivation has been shown to affect this function. The objective of our study was to assess the effects of sleep-disordered breathing (SDB) on postural stability. Methods: 158 subjects referred for suspected SDB had an overnight sleep study and were placed on a posturographic platform in late afternoon. This platform allows measuring the centre of pressure ( CoP ) oscillations and to calculate: total displacement of CoP in X and Y axes, mean speed of CoP displacement and the length as function of surface (LFS) ratio (length of CoP displacement/surface of CoP trajectory). Results: 98 men and 60 women were included. Mean age±SD was 45.4±5.5 years old, body mass index (BMI) 27.5±5.6 kg/m 2 and apnoea–hypopnoea index (AHI) 13.6±16.1/h. AHI was <5/h in 64 (41%) subjects, 5–15/h in 43 (27%), 15–30/h in 30 (19%) and >30/h in 21 (13%). In patients with an AHI >5/h versus AHI <5/h, we observed an important increase in LFS (+21%, p<0.001), in XY length (+23%, p<0.001) and in mean speed (+23%, p<0.001). After controlling for age, BMI and sleepiness (Epworth) in multivariate regression models, there was a positive association between all nocturnal breathing parameters (specifically: mean SpO2, AHI, oxygen desaturation index 3% and % time with SpO2 <90%) and the main stability outcomes (all p<0.05). Conclusions: SDB severity, especially the mean nocturnal SpO2 level, is associated with impaired daytime postural stability.